1992
DOI: 10.1073/pnas.89.13.6192
|View full text |Cite
|
Sign up to set email alerts
|

Rapid decline of chronic myeloid leukemic cells in long-term culture due to a defect at the leukemic stem cell level.

Abstract: In this report we describe a quantitative in vitro assay for the most primitive type of leukemic precursors yet defined in patients with chronic myeloid leukemia (CML). This assay is based on the recently described "long-term culture-initiating cell" (LTC-IC) assay for primitive normal human hematopoietic cells. Such cells, when cocultured with competent fibroblast feeder layers, give rise after a minimum of 5 weeks to multiple single and multilineage clonogenic progenitors detectable in secondary semisolid as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
95
1
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(104 citation statements)
references
References 23 publications
7
95
1
1
Order By: Relevance
“…Opinions range from the one extreme, that the great recently been used by Maguer-Satta et al 29 They studied five majority of primitive cells are Ph − , to the other, that many CML patients in whom the primitive cell compartment (LTCIC) are Ph + at least in some patients. 11,[13][14][15][16][17]29,30 However, recent was known to consist predominantly of Ph + cells. By sorting studies demonstrating the existence in CML patients of leuprimitive cells and performing RT-PCR on them individually kemic cells that are capable of reconstituting severe combined they found that BCR/ABL mRNA could be specifically immunodeficient mice, 31 and the well-demonstrated transdetected in about 60-90% of the CML cells in which the actin forming activity of BCR-ABL in experimental systems, [32][33][34] message was present.…”
Section: Resultsmentioning
confidence: 99%
“…Opinions range from the one extreme, that the great recently been used by Maguer-Satta et al 29 They studied five majority of primitive cells are Ph − , to the other, that many CML patients in whom the primitive cell compartment (LTCIC) are Ph + at least in some patients. 11,[13][14][15][16][17]29,30 However, recent was known to consist predominantly of Ph + cells. By sorting studies demonstrating the existence in CML patients of leuprimitive cells and performing RT-PCR on them individually kemic cells that are capable of reconstituting severe combined they found that BCR/ABL mRNA could be specifically immunodeficient mice, 31 and the well-demonstrated transdetected in about 60-90% of the CML cells in which the actin forming activity of BCR-ABL in experimental systems, [32][33][34] message was present.…”
Section: Resultsmentioning
confidence: 99%
“…Nine of these twelve patients were then treated with a-interferon (IFN-a) 1-3 x lo6 units/m2, 3-7 dayslweek; four returned to complete remission, three developed increasing numbers of Ph+ cells, and two are still too early to evaluate. Recently, we have shown that leukemic stem cells, operationally defined as Ph+ LTC initiating cells (LTC-IC), are, on average, present in CML marrow at levels 10-fold lower than their normal counterparts and can be selectively "purged" (by a factor of 30-fold) following incubation for 10 days in LTC [5,6].…”
mentioning
confidence: 99%
“…Initially, the finding that such cells were present in markedly elevated numbers in the peripheral blood, as anticipated from previous studies of clonogenic cells, led to the expectation that their numbers might be similarly elevated in the marrow. In fact, the opposite appears to be the case [19] (see also Fig. IB).…”
Section: Quantitation Of Normal and CML Stem Cellsmentioning
confidence: 85%
“…The most dramatic differential effect of any treatment thus far examined appears to be that afforded by simply placing a CML marrow autograft in culture for a period of 7 to 10 days [19]. Under these conditions, normal LTC-IC numbers remain at, or may even increase to slightly above, input numbers whereas the Ph-positive LTC-IC decline precipitously, on average by a factor of -30 (Fig.…”
mentioning
confidence: 99%